THE EFFECTIVENESS OF COMBINATION OF OXYTOCIN AND ENDORPHIN MASSAGE ON UTERINE INVOLUTION IN PRIMIPAROUS MOTHERS - Nurmala Sari; Ariawan Soejoenoes; Sri Wahyuni; Onny Setiani; Choiroel Anwar (Belitung Raya Foundation, Indonesia, 2017)
Background: One of the puerperal complications is uterine subinvolution that can cause bleeding to maternal death. Oxytocin massage can stimulate oxytocin hormone that plays a role in the process of uterine involution. Endorphin massage can increase the release of oxytocin and endorphin hormone that give a sense of calm and comfort. It also increases production of oxytocin hormone that can improve the process of uterine involution. Objective: To prove the effectiveness of a combination of oxytocin massage and endorphin massage to uterine involution in primiparous mothers during postpartum period. Methods: This was a quasi-experimental study with pretest-posttest with control group design. Total samples were 44 normal postpartum mothers selected using purposive sampling technique, which were randomly assigned in four groups, namely: 1) oxytocin massage group, 2) endorphin massage group, 3) combined oxytocin-endorphin massage group, and 4) control group. Data were analyzed using univariate, bivariate and One-Way ANOVA to test the effectiveness of the intervention. Results: There were statistically significant differences of fundal height before and after intervention among the four groups (p=<0.05). Conclusion: The combination of oxytocin massage and endorphin massage proved most effective in accelerating uterine involution in normal postpartum mothers.